A microfluidics platform for simultaneous evaluation of sensitivity and side effects of anti-cancer drugs using a three-dimensional culture method - Yuki Kobayashi; Honoka Hashizume; Sotaro Takiguchi; Jiajue Ji; Ryuji Kawano; Keiichiro Koiwai; Haru Yamamoto; Mohamed Elbadawy; Tsutomu Omatsu; Amira Abugomaa; Masahiro Kaneda; Tatsuya Usui; et al. (Scientific Reports)
Abstract Organoids are stem cell-derived three-dimensional tissue cultures composed of multiple cell types that recapitulate the morphology and functions of their in vivo counterparts. Organ-on-a-chip devices are tiny chips with interconnected wells and channels designed using a perfusion system and microfluidics to precisely mimic the in vivo physiology and mechanical forces experienced by cells in the body. These techniques have recently been used to reproduce the structure and function of organs in vitro and are expected to be promising alternatives for animal experiments in the future. In the present study, we designed and fabricated an organ-on-a-chip system for mounting organoids from mammary tumor-affected cats (FMT organoids) and normal intestinal organoids from mice (MI organoids) and perfused them with anti-cancer drugs. The effects of drug perfusion on FMT and MI organoids were examined by measuring cell viability and performing genetic analysis. After 48 h of perfusion with toceranib (10 µM) or doxorubicin (1 µM), cell viability of FMT organoids was decreased compared to the non-perfusion condition. The expression of apoptosis-related genes, such as p53 and Caspase-9 was significantly upregulated in FMT organoids with drug perfusion. The rate of cell death drastically differed before and after branching in the device, owing to differences in flow velocity and drug infiltration. Perfusion of MI organoids with toceranib also reduced viability, as observed in FMT organoids; however, this was due to the induction of necrosis rather than apoptosis. In conclusion, our established multi-organoid-on-chip system could be used to evaluate anti-cancer drug sensitivity and side effects in vitro, which might contribute to developing personalized medicine for cancer patients.